THE TRIPLE HELIX MODEL: UNIVERSITY-INDUSTRY-GOVERNMENT COLLABORATION AND ITS ROLE IN SMES INNOVATION AND DEVELOPMENT - Adih Supriadi; Indra Permana; Dian Rachmawati Afandi; Edy Arisondha; Ani Kusumaningsih (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The Triple Helix Model, fostering collaborative synergy among universities, industries, and government entities, emerges as a fundamental framework for propelling innovation and development within Small and Medium Enterprises (SMEs). This comprehensive literature review meticulously explores the model's historical evolution, delves into its theoretical underpinnings, and examines its practical applications in the unique context of Indonesian SMEs. Dissecting the nuanced roles played by universities, industries, and government entities underscores their collective contribution to shaping a knowledge-based society. A thorough examination of government initiatives, insightful case studies, and the integrative impact of the Triple Helix Model in SME development illuminate the transformative dynamics at play. The discussion extends to encompass methodologies for measuring impact, key performance indicators, and the nuanced influences of regional factors. Anticipated trends and forward-looking recommendations for future research and policy development underscore the model's pivotal role in steering the trajectory of SMEs in Indonesia, establishing them as indispensable contributors to the ever-evolving landscape of innovation and sustainable development.